In Vivo Effects on Stress Protein, Genotoxicity, and Oxidative Toxicity Parameters in Oreochromis niloticus Tissues Exposed to Thiamethoxam - KARĞIN, DİCLE (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
This study aimed to observe the effect of toxicity of the pesticide thiamethoxam (TMX) at sublethal concentrations in the liver and brain of Oreochromis niloticus. In the experiment, fish were exposed to 50, 100, and, 150 mg/L with thiamethoxam for 48 h and 15 days. The superoxide dismutase (SOD), catalase (CAT), glutathione S-transferaz (GST), glutathione peroxidase (GPx), and ethoxyresorufin-O-deethylase (EROD) activities; and thiobarbituric acid reactive substance (TBARS), heat shock proteins 70 (HSP70), glutathione (GSH), and genotoxicity parameter 8-hydroxy-2 '-deoxyguanosine (8-OHdG) were analyzed by spectrophotometric methods and ELISA techniques. Depending on time and dose in TMX exposure in liver tissue, a significant decrease in GSH level; an increase in SOD, GST, GPx, and EROD enzyme activities; and HSP70, TBARS, and 8-OHdG levels was determined. In brain tissue, SOD, GST, and EROD enzyme activities, an increase in HSP70, TBARS, and 8-OHdG levels, and a decrease in CAT enzyme activity and GSH levels were determined. In this study, TMX in the concentrations used showed that changes in oxidative stress biomarkers, genotoxicity parameter 8-OHdG levels, and HSP70 levels caused toxic effects in the model organism. As a result of the study, the changes and protective effects of the antioxidant system and stress proteins at the cellular level were determined in sublethal doses of toxic effects caused by TMX in the vital organs of the organism. In this toxicological study, TMX exposure resulted in toxicity to O. niloticus liver and brain tissues, in addition, responses of biomarkers to time and concentrations were determined. As a result of this study, the potential toxic effects of the commonly used pesticide TMX will reveal both the ecological risks of the aquatic organism and the basic data of the safety and risk assessments of O. niloticus consumed as food for human health.
Keywords: Pesticide; Thiamethoxam; Oreochromis niloticus; HSP70; 8-OHdG; FRESH-WATER FISH; HEAT-SHOCK PROTEINS; DNA-DAMAGE; CHANNA-PUNCTATUS; NILE-TILAPIA; ACETYLCHOLINESTERASE ACTIVITY; ANTIOXIDANT SYSTEM; LIPID-PEROXIDATION; CARASSIUS-AURATUS; AQUATIC ORGANISMS